MUSIC AT MMABANA CULTURAL CENTRE, P.O. Box X2170, Mafikeng, Bophuthatswana (South Africa). Achilles Mukasa Bukenya writes (International Library of African Music, 1992)
Mmabana is a unique establishment in that under its roof is housed a wide spectrum of disciplines, social services and activities designed to give the members of the community education, self-development, recreation and entertainment. One such facility is the Music Unit, whose aims are, among others, to provide its participants with a balanced music programme which will enable them to develop their musical talent, enhance their interest in the subject and give them the opportunity of making and enjoying music together.
Keywords: South Africa; African Music